Outlier detection of time series with a novel hybrid method in cloud computing. (19th September 2019) - Liu, Qi; Wang, Zhen; Liu, Xiaodong; Linge, Nigel
In the wake of the developments in science and technology, cloud computing has obtained more attention in different fields. Meanwhile, outlier detection for data mining in cloud computing is playing significant role in different research domains and massive research works have been devoted to outlier detection. However, the existing available methods require lengthy computation time. Therefore, the improved algorithm of outlier detection, which has higher performance to detect outliers, is presented. In this paper, the proposed method, which is an improved spectral clustering algorithm (SKM++), is fit for handling outliers. Then, pruning data can reduce computational complexity and combine distance-based method Manhattan distance ( distm ) to obtain outlier score. Finally, the method confirms the outlier by extreme analysis. This paper validates the presented method by experiments with real collected data by sensors and comparison against the existing approaches. The experimental results show that our proposed method outperforms the existing.